Optimizing the decellularization process of human maxillofacial muscles for facial reconstruction using a detergent‐only approach. (25th July 2019) - Naik, Anish; Griffin, Michelle F.; Szarko, Matthew; Butler, Peter E.
Abstract: Trauma, congenital diseases, and cancer resection cause muscle deformities of the human facial muscle. Muscle defects are either treated with local or distal flaps if direct closure is not possible. However, such surgical interventions are limited by donor morbidity and limited tissue availability. Decellularized scaffolds provide alternative strategies for replacing and restoring missing facial muscle by creating scaffolds that mimic the native tissue. This study aimed to develop a protocol to decellularize human zygomaticus major muscle (ZMM) and masseter muscle (MM). Three protocols were assessed including a detergent‐only treatment (DOT), detergent‐enzymatic treatment (DET) protocol, and a third nondetergent nonenzymatic treatment protocol. Scaffolds were then characterized via histological, immunofluorescent, and quantitative techniques to assess which protocol provided optimal decellularization and maintenance of the extracellular matrix (ECM). The results demonstrated three cycles of DOT protocol consisting of 2% sodium dodecyl sulfate for 4 hr was optimal for decellularization for both ZMM and MM. After three cycles, DNA content was significantly reduced compared with native ZMM and MM ( p < .05) with preservation of collagen and glycosaminoglycan content and ECM on histological analysis. DET and nondetergent nonenzymatic treatment protocols were unsuccessful in decellularizing the ZMM and MM with residual DNA content after four cycles and caused ECM disruption on histological analysis. All protocols did not impair the mechanical properties and supported human fibroblast growth. In conclusion, the DOT protocol is effective in producing human decellularized muscle scaffolds that maintain the ECM. Further investigation of detergent only decellurization techniques should be explored as a first step to create effective scaffolds for muscle tissue engineering.